2017
DOI: 10.1155/2017/1309053
|View full text |Cite
|
Sign up to set email alerts
|

Combining Resistivity and Aeromagnetic Geophysical Surveys for Groundwater Exploration in the Maghnia Plain of Algeria

Abstract: The Maghnia plain in western Algeria is filled by Plio-Quaternary and Miocene sediments that rest unconformably on a basement of Jurassic rocks. Electrical sounding (VES), magnetic data, well information, and hydrogeological data have been used to explore for groundwater potential in the Maghnia plain. The interpretation of Schlumberger sounding data was first calibrated with the lithology of available nearby wells. Four geoelectrical layers were identified within the study area. They are a thin near surface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As shown in The actual groundwater status has not changed significantly compared to the study period; the Hydrographical Basin Agency's reports have revealed that the actual situation of groundwater has been marked by continuous decreases in water quality caused by the synergistic effects of drought, changing land use, pollution from agriculture and industrialization, as well as from natural processes (weathering of soil and rock) (ABHOCC 2009a(ABHOCC , b, 2012(ABHOCC , 2016. Current groundwater use practices have led to overexploitation of some aquifers in Tafna basin (e.g., aquifer of Maghnia); some aquifers in the Coastal Oranais basin have also not escaped overexploitation with the Bredeah and Coastal Oranais Plain aquifers suffering from saltwater intrusion (Dahmani and Bithorel 2001;Gaaloul et al 2012;Adjim and Bensaoula 2013;Boubaya 2017;Alfarrah and Walraevens 2018). The continuous monitoring of groundwater is required to get the recent groundwater quality status to check any possible contamination in future due to growing industrialization and agricultural activities; the influence of salt water on the some freshwater aquifers in the study area needs special attention in terms of monitoring and for sustainable management.…”
Section: Wqi For Drinking Water Assessmentmentioning
confidence: 99%
“…As shown in The actual groundwater status has not changed significantly compared to the study period; the Hydrographical Basin Agency's reports have revealed that the actual situation of groundwater has been marked by continuous decreases in water quality caused by the synergistic effects of drought, changing land use, pollution from agriculture and industrialization, as well as from natural processes (weathering of soil and rock) (ABHOCC 2009a(ABHOCC , b, 2012(ABHOCC , 2016. Current groundwater use practices have led to overexploitation of some aquifers in Tafna basin (e.g., aquifer of Maghnia); some aquifers in the Coastal Oranais basin have also not escaped overexploitation with the Bredeah and Coastal Oranais Plain aquifers suffering from saltwater intrusion (Dahmani and Bithorel 2001;Gaaloul et al 2012;Adjim and Bensaoula 2013;Boubaya 2017;Alfarrah and Walraevens 2018). The continuous monitoring of groundwater is required to get the recent groundwater quality status to check any possible contamination in future due to growing industrialization and agricultural activities; the influence of salt water on the some freshwater aquifers in the study area needs special attention in terms of monitoring and for sustainable management.…”
Section: Wqi For Drinking Water Assessmentmentioning
confidence: 99%
“…Magnetic data can be acquired on ground, in air, and in marine; however, the regional study requires aeromagnetic data. Aeromagnetic data is an essential tool in delineation of Basement rocks and estimation of depth to magnetic sources, even in sedimentary terrain without being disturbed by obstacles [61][62][63][64].…”
Section: Methodsmentioning
confidence: 99%
“…It also contains shallow calcium formations (Luvisols) and alluvial marshland (fluvisols) developed in the northern part of the Maghnia plain. The southern part of the plain comprises red soils (arenosols) to crusting formed from saliferous marnes of the Miocene [Boubaya, 2017].…”
Section: Presentation Of the Study Sitementioning
confidence: 99%